FREQUENCY OF HBs Ag AND ANTI-HCV IN ANTENATAL POPULATION - Rubina Sabir; Ozma Noor Osman (Journal of University Medical & Dental College, 2013)
ABSTRACT OBJECTIVE: To determine the frequency of HBsAg and anti-HCV in pregnant women. STUDY DESIGN: Class Sectional descriptive study conducted at patients and methods. Total 5172 pregnant women enrolled in the study. Venous blood was collected for HBs Ag and HCV antibodies detection by ELISA. RESULT: All n=5172 pregnant women were tested for HBs Ag and anti HCV were divided into 6 groups according to age. In 1st group 15–20 years, n=714, 7 (7.8%) HBs Ag and 39 (9.2%) Anti HCV, in 2nd group 20–25 years, n=1715, 12 (13.3%) HBs Ag and 52 (12.3%) Anti HCV, in 3rd group 26–30 years, n=1168, 17 (18.9%) HBs Ag and 82 (19.4%) anti HCV, in 4th group 31–35 years, n=616, 19 (21.1%) HBs Ag and 89 (21%) anti HCV, in 5th group 36–40 years, n=579, 16 (17.8%) HBs Ag and 77 (18.2%) anti HCV and in 6th group 41–45 years, n=362, 19 (21.1%) HBs Ag and 84 (19.9%) anti-HCV positive results. DISCUSSION: According to a present study there was a high frequency of anti-HCV 8.78% than HBs Ag 1.74% among antenatal subjects of Karachi which were higher than previous Published local studies.